Endothelial FAK is required for tumour angiogenesis. Issue 10 (October 2016) - Tavora, Bernardo; Batista, Silvia; Reynolds, Louise E; Jadeja, Shalini; Robinson, Stephen; Kostourou, Vassiliki; Hart, Ian; Fruttiger, Marcus; Parsons, Maddy; Hodivala‐Dilke, Kairbaan M
Abstract :